2015
DOI: 10.4028/www.scientific.net/amr.1125.69
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Moisture Absorption Effects on the Strength of Composite Materials

Abstract: In the present work, the variation of the tensile strengths of various polymers and polymer composites due to moisture ageing is investigated. The stacking sequences of the composites include 0o, 90o, ±45o and quasi-isotropic laminates. The variation in the strength of material is then fitted using a residual property model. Results show that the proposed model characterises well the variation in the strengths that exhibits a typical trend, where there is no obvious scattered data. In fibre dominated laminates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…5, it was noticed that all properties (strength, energy, and stiffness) degraded with the increase in moisture content. This was consistent with the general observation and all data was hence fitted using the residual property model (RPM) proposed previously by Wong et al [16]. Results showed a good fit for the different properties considered.…”
Section: Effects Of Quasi-static Loading On Adhesive Joint Under Moissupporting
confidence: 90%
See 1 more Smart Citation
“…5, it was noticed that all properties (strength, energy, and stiffness) degraded with the increase in moisture content. This was consistent with the general observation and all data was hence fitted using the residual property model (RPM) proposed previously by Wong et al [16]. Results showed a good fit for the different properties considered.…”
Section: Effects Of Quasi-static Loading On Adhesive Joint Under Moissupporting
confidence: 90%
“…In order to characterize the variation of mechanical properties of the adhesive joints tested due to moisture absorption, the residual property model (RPM) proposed by Wong et al [16] is adopted. RPM describes that the normalized residual property can be predicted using the following equation:…”
Section: Effects Of Quasi-static Loading On Adhesive Joint Under Moismentioning
confidence: 99%
“…To describe the variation of G IIC with respect to moisture content M , the following residual property model (RPM) [ 3 , 6 , 13 ] is adopted where G IIC (M) is the residual mode II fracture toughness at particular moisture content, G IIC,dry is the dry property, G IIC,min is lowest mode II fracture toughness within the range of study, M is the moisture content, M m is the maximum moisture content, and ζ is the degradation parameter. This model assumes that the residual mode II fracture toughness is a function of moisture content only.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, aircraft structures are exposed to different environmental conditions throughout their service lifetime. It is commonly reported that moisture absorption could lead to the degradation in the mechanical properties of composite materials [ 3 , 4 , 5 , 6 ]. Not only that, as the external loadings in real life applications are generally induced in the lateral direction, mode II delamination could be dominant due to the interlaminar shear stress caused by the bending of the structures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…When using carbon/epoxy laminated composites for aircraft applications, the materials are inevitably subjected to various environmental conditions. Upon prolonged moisture and heat attacks, the properties may degrade and lead to premature failure of the structures [ 3 , 4 , 5 , 6 , 7 ]. It is common to relate the residual properties to the absorbed moisture content of the materials [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%